1981
DOI: 10.1071/ar9810839
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of breeds and their crosses for beef production. II. Growth and puberty of heifers

Abstract: Semen from Hereford (H), Friesian (F), Charolais (C) and Brahman (B) bulls was used to inseminate H and F cows in August and September of each year from 1970 to 1973. After weaning at 8 months of age, the heifer progeny were grazed on improved pastures and oestrus was detected by sterilized bulls fitted with chin-ball harnesses. Average daily liveweight gains (kg/day) from weaning to 21 months and liveweights (kg) at 21 months were: HH, 0.44, 373 ; FH, 0.47, 402; CH, 0.47,402; BH, 0.45, 374; HF, 0.42, 428; FF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The genotype differences observed on high pasture are consistent with the results of Laster et al (1976) for S x H v. H x H; Gregory et al (1979) for B x H v. Hereford-Angus cross; and Morgan (1981) for F x H v. H x H. However, Deland, Jakes & Giles (1974), and Morgan (1981) observed little difference in growth rate between B x H and H x H heifers in southern Australia. It is evident that B x H heifers grew relatively faster during the summer months, on poorer nutrition in Nebraska (Gregory et al 1979), and Deland et al (1983) observed a similar pattern of growth with steers in South Australia.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The genotype differences observed on high pasture are consistent with the results of Laster et al (1976) for S x H v. H x H; Gregory et al (1979) for B x H v. Hereford-Angus cross; and Morgan (1981) for F x H v. H x H. However, Deland, Jakes & Giles (1974), and Morgan (1981) observed little difference in growth rate between B x H and H x H heifers in southern Australia. It is evident that B x H heifers grew relatively faster during the summer months, on poorer nutrition in Nebraska (Gregory et al 1979), and Deland et al (1983) observed a similar pattern of growth with steers in South Australia.…”
Section: Discussionsupporting
confidence: 82%
“…Genotype differences have been documented for weight at puberty: H x H, 274-290;S x H, 286;F x H, 263;and B x H, 332-336 kg (Laster et al 1976;Gregorys al. 1979;Morgan, 1981). For a high proportion of heifers (85 %) to be sexually mature, mean live weights need to be about 40 kg higher than these values (Laster et al 1976;Gregory et al 1979;Cohen, Garden & Langlands, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that age and weight at puberty differ among various cattle breeds (Reynolds et ai., 1963;Kennedy and Chirchir, 1971;Brown et al, 1972;Laster et al, 1972Laster et al, , 1976Swierstra et al, 1977;Young et al, 1978;Gregory et al, 1979Gregory et al, , 1982Morgan, 1981;Steffan et al, 1985); effects of nutrition on the growing heifer are well documented (Joubert, 1954;Crichton et al, 1959;Wiltbank et al, 1962Wiltbank et al, , 1965Wiltbank et al, , 1969Wiltbank et al, , 1985Bellows et al, 1965;Arije and Wiltbank, 1971;Short and Bellows, 1971;Vamer et al, 1977;Laster et al, 1979;Fleck et al, 1980;Lemanager et al, 1980;Ferrell, 1982). Interactions between genotypic groups and environmental variables, including breeds, breed crosses, and lines or strains within a bred that evolved in different environments, also have been reported (Cartwright, 1955;Rollins et al, 1963;Butts et al, 1971;Kress et al, 1971a,b;Burns et al, 1979;Koger et al, 1979).…”
Section: Lntroductlonmentioning
confidence: 99%
“…Breed differences have been reported for the age and weight at puberty (Gregory et al 1991;Burns et al 1992;Martin et al 1992;Thallman et al 1999) and specifically, Bos indicus breeds (e.g. Brahmans) have been reported to be older at puberty than other breeds Morgan 1981;Bolton et al 1987;Hearnshaw et al 1994;Thallman et al 1999). Several studies have shown that the age at puberty was heritable in Bos taurus breeds of beef cattle (MacNeil et al 1984;Gregory et al 1995).…”
Section: Introductionmentioning
confidence: 99%